Development of a Holistic Partnership Model of Character Education Based on Android Applications for Junior High School Students - Febiantoni, Fungki Febiantoni; cucu sutrisno; Mukhamad Murdiono; Yayuk Hidayah; Dian Satria Charismana (Golden Ratio of Social Science and Education, 2025)
The strengthening of character education in schools needs to be implemented collaboratively by involving the roles of students' parents and/or families and the community. To facilitate such partnership initiatives, a partnership model is required as a shared reference and a parameter for achieving its implementation. This study aims to develop a character education partnership model for junior high school students based on an Android application. This research is a development study referring to the procedures outlined by Borg and Gall (2007), which consist of ten stages. In this second stage, the research involved the development of an initial product following the data collection and planning stages conducted in the previous year. During this initial product development stage, an Android application was developed to implement the holistic character education partnership model for junior high school students. After the initial product design was formed, experts, including material and media experts, conducted a preliminary field test. The results of the expert validation were used to improve or revise the product before conducting further limited user testing. The result of this study is Prototype 1 of the Android application titled "Ketik Pintar Apps" (Holistic Character Education Partnership Application). This application facilitates the implementation of the holistic character education partnership model for junior high school students by accommodating elements of holistic partnership, such as communication, participation, and empowerment of teachers and parents in an integrated, simultaneous, and persistent manner in the implementation of character education both at school and outside of school.